Rural Women in Development: The Role and Challenges of Female Participation in Suwangi Village, Indonesia - Maemunah Maemunah; Abdul Sakban; Isnaini Isnaini; Delisa Aprionika (Jurnal Ilmu Sosial dan Humaniora, 2025)
Rural women play an essential yet often invisible role in village development, especially in regions where cultural and religious norms define gendered participation. This qualitative study, conducted in Suwangi Village, East Lombok, involved ethnographic observations and semi-structured interviews with 15 informants, including female officials, religious and customary leaders, and community members. Findings show that around 85% of women engage in micro-economic activities such as food processing and home-based trading, 80% participate in social organizations (PKK and Posyandu), yet less than 20% are represented in formal village decision-making forums. Despite these disparities, new opportunities are emerging through female role models, inclusive religious discourse, and reinterpretations of adat norms. The study reveals that Sasak cultural identity and Islamic values simultaneously constrain and enable women’s public participation—religious and customary leaders now serve as crucial mediators legitimizing gender equality within local development frameworks. Scientifically, this study contributes to the discourse on gender and development by providing empirical micro-level evidence from a culturally specific Muslim community, illustrating how gendered agency evolves through the interaction of tradition, religion, and institutional structures. It advances theoretical understanding of contextualized empowerment, showing that bottom-up, culturally rooted strategies can complement formal gender mainstreaming policies. The findings highlight the importance of integrating local cultural legitimacy into gender-inclusive rural governance models, particularly in areas shaped by strong religious and customary traditions like East Lombok.